Resin composition, copper foil with resin, and printed wiring board
By blending resin compositions of arylene ether compounds, styrene-based copolymers and liquid crystal polymers, the problem of dielectric loss and adhesion reduction in resin layer in high-frequency printed circuit boards is solved, and a resin composition with low dielectric loss and high adhesion is achieved, and signal transmission quality is improved.
Patent Information
- Application Number
- CN202380054471.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-08-01
- Publication Date
- 2025-03-11
AI Technical Summary
In high-frequency printed circuit boards, it is difficult for the existing resin layer to effectively suppress dielectric loss, and the adhesion decreases after heat treatment, affecting signal transmission quality.
By blending organic fillers composed of arylene ether compounds, styrene-based copolymers and liquid crystal polymers, a resin composition is prepared. The resin composition exhibits a low dielectric loss tangent at 10 GHz and has high adhesion on a low roughness surface, which can stably maintain high adhesion after thermal load.
This resin composition not only reduces transmission losses in high-frequency circuits, but also maintains high adhesion after heat treatment, significantly improving the signal transmission quality of the printed circuit board.
Smart Images

Figure BDA0005246638100000051 
Figure BDA0005246638100000171 
Figure BDA0005246638100000181
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a copper foil with resin and a printed wiring board. Background Art
[0002] Printed wiring boards are widely used in electronic devices, etc. In particular, with the increase in functionality of electronic devices, etc. in recent years, the frequency of signals is also getting higher and higher, and high-speed and large-capacity communication has become possible. As examples of such uses, communication servers, car automatic driving, mobile phones supporting 5G, etc. can be cited. The demand for printed wiring boards suitable for such high-frequency uses is growing. For this high-frequency printed wiring board, it is desired to have low transmission loss so that high-frequency signals can be transmitted without reducing their quality. The printed wiring board is equipped with a copper foil and an insulating resin substrate processed into a wiring pattern, and the transmission loss mainly includes the conductor loss caused by the copper foil and the dielectric loss caused by the insulating resin substrate. Therefore, in the copper foil with a resin layer suitable for high-frequency use, it is desired to suppress the dielectric loss caused by the resin layer. For this reason, the resin layer is required to have excellent dielectric properties, particularly low dielectric loss tangent.
[0003] On the other hand, various resin compositions with excellent dielectric properties and adhesion have been proposed for use in printed circuit boards and the like. For example, Patent Document 1 (International Publication No. 2013 / 105650) discloses a copper foil with an adhesive layer, which has an adhesive layer on one side of the copper foil, and the adhesive layer is formed by a resin composition comprising a styrene-butadiene block copolymer of 5 parts by mass and 65 parts by mass or less relative to 100 parts by mass of a polyphenylene ether compound. In addition, Patent Document 2 (International Publication No. 2016 / 175326) discloses a resin composition comprising: a polyphenylene ether derivative (A) having a group containing an N-substituted maleimide structure in one molecule; at least one thermosetting resin (B) selected from the group consisting of an epoxy resin, a cyanate resin and a maleimide compound; and a styrene-based thermoplastic elastomer (C). Patent document 3 (Japanese Patent Application Publication No. 2011-225639) discloses a thermosetting resin composition comprising an uncured semi-IPN type composite and (D) a radical reaction initiator. It is described that the uncured semi-IPN type composite is an uncured product obtained by compatibilizing (A) a polyphenylene ether with a prepolymer composed of (B) a butadiene polymer and (C) a crosslinking agent, wherein the (B) butadiene polymer contains 40% or more of 1,2-butadiene units in the molecule, and the 1,2-butadiene units have 1,2-vinyl groups in the side chains.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2013 / 105650
[0007] Patent Document 2: International Publication No. 2016 / 175326
[0008] Patent Document 3: Japanese Patent Application Publication No. 2011-225639 Summary of the invention
[0009] The inventors of the present invention have studied the resin composition as excellent in dielectric properties and the like and pasted it as a primer layer (adhesive layer) on base materials such as prepreg. In addition, the layer of the resin composition is provided in the form of a copper foil with resin, and the copper foil can be used as a circuit forming copper foil. The resin composition expected to be used for the above-mentioned purposes not only has excellent dielectric properties, but also has excellent adhesion to low roughness surfaces (such as the surface of low roughness copper foil). In particular, when forming a circuit for high frequency, from the viewpoint of reducing transmission loss, it is expected to be a low roughness copper foil, but because this copper foil is low roughness, there is a tendency to reduce the adhesion with the resin composition. In particular, when heat-treated in the substrate manufacturing process, there is a tendency that the adhesion of copper foil and the resin composition further decreases. Therefore, the resin composition expected to be used for the above-mentioned purposes not only shows excellent dielectric properties and high adhesion to low roughness surfaces (such as the surface of low roughness copper foil), but also can stably maintain high adhesion after heat load.
[0010] This time, the present inventors have obtained the following insight: by blending a specified arylene ether compound and / or a specified styrene-based copolymer, and an organic filler composed of a liquid crystal polymer, it is possible to provide a resin composition that not only exhibits excellent dielectric properties (for example, a low dielectric loss tangent at 10 GHz) and high adhesion to low-roughness surfaces (for example, the surface of a low-roughness copper foil), but also can stably maintain high adhesion after heat loading.
[0011] Therefore, an object of the present invention is to provide a resin composition which not only exhibits excellent dielectric properties and high adhesion to a surface with low roughness but also can stably maintain high adhesion even after heat load.
[0012] According to the present invention, the following aspects are provided.
[0013] [Method 1]
[0014] A resin composition comprising:
[0015] at least one of an arylene ether compound having a weight average molecular weight of 30,000 or more and a styrene-based copolymer having a reactive unsaturated bond in the molecule that exhibits reactivity by heat or ultraviolet rays, and
[0016] Organic fillers composed of liquid crystal polymers.
[0017] [Method 2]
[0018] The resin composition according to embodiment 1, wherein the reactive unsaturated bond is at least one selected from the group consisting of a cyanate group, a maleimide group, a terminal vinyl group, a (meth)acryloyl group, an ethynyl group, and a styryl group.
[0019] [Method 3]
[0020] The resin composition according to embodiment 1 or 2, wherein the styrene-based copolymer has a styrene group as the reactive unsaturated bond.
[0021] [Method 4]
[0022] The resin composition according to any one of aspects 1 to 3, wherein the resin composition contains both the arylene ether compound and the styrene-based copolymer.
[0023] [Method 5]
[0024] The resin composition according to any one of aspects 1 to 4, wherein the organic filler has a dielectric loss tangent of 0.001 or less at a frequency of 10 GHz.
[0025] [Method 6]
[0026] A copper foil with resin includes: a copper foil; and a resin layer including the resin composition according to any one of aspects 1 to 5, which is provided on at least one surface of the copper foil.
[0027] [Method 7]
[0028] The resin-attached copper foil according to Embodiment 6, wherein a ten-point height Rzjis of microscopic roughness measured in accordance with JIS B0601-2001 at a surface of the copper foil on the resin layer side is 2.0 μm or less.
[0029] [Method 8]
[0030] A printed circuit board is made using the copper foil with resin described in method 6 or 7. DETAILED DESCRIPTION
[0031] Resin composition
[0032] Resin composition of the present invention comprises: at least one of arylene ether compound and styrene copolymer, and organic filler.Arylene ether compound has weight average molecular weight more than 30000, and styrene copolymer has reactive unsaturated bond that shows reactivity by heat or ultraviolet in molecule.Organic filler is made of liquid crystal polymer.Like this, by blending the arylene ether compound and / or the styrene copolymer of regulation and the organic filler made of liquid crystal polymer, it is possible to provide the resin composition that not only shows excellent dielectric properties (such as low dielectric loss tangent at 10GHz) and high adhesion to low roughness surface (such as surface of low roughness copper foil), but also can stably maintain the adhesion after heat load.
[0033] As mentioned above, the present inventors have studied the resin composition as excellent in dielectric properties and pasted it as primer layer (adhesive layer) on base materials such as prepreg. And, the layer of the resin composition is provided in the form of copper foil with resin, and the copper foil can be used as copper foil for circuit formation. The resin composition for the above-mentioned purpose is not only expected to have excellent dielectric properties, but also excellent in adhesion to low roughness surface (such as the surface of low roughness copper foil). Especially, when forming a circuit for high frequency, from the viewpoint of reducing transmission loss, it is expected to be low roughness copper foil, but because this copper foil is low roughness, there is a tendency to reduce the adhesion of the resin composition. Especially, in the case of heat treatment in the substrate manufacturing process, there is a tendency that the adhesion of copper foil and the resin composition further decreases. For this point, by the resin composition of the present invention, the above-mentioned problems can be overcome smoothly.
[0034] The resin composition of the present invention contains at least one of an arylene ether compound having a weight average molecular weight of 30,000 or more and a styrene copolymer having a reactive unsaturated bond in the molecule that exhibits reactivity by heat or ultraviolet rays, but preferably contains both the arylene ether compound and the styrene copolymer. Thus, the above-mentioned effects brought about by the present invention can be more effectively achieved.
[0035] The dielectric loss tangent of the resin composition of the present invention at a frequency of 10 GHz after curing is preferably less than 0.0035, more preferably less than 0.0020, and further preferably less than 0.0015. The dielectric loss tangent is preferably low, and the lower limit is not particularly limited, but is usually 0.0001 or more.
[0036] The resin composition of the present invention preferably contains an arylene ether compound. The weight average molecular weight of the arylene ether compound is 30,000 or more, preferably 30,000 or more and 300,000 or less, more preferably 40,000 or more and 200,000 or less, and particularly preferably 45,000 or more and 120,000 or less. The arylene ether compound having a weight average molecular weight of 30,000 or more is preferably a phenylene ether compound, such as a polyphenylene ether. The arylene ether compound or the phenylene ether compound is preferably a compound containing a skeleton shown by the following chemical formula in the molecule.
[0037]
[0038] (wherein R1, R2, R3 and R4 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms)
[0039] Examples of phenylene ether compounds include styrene derivatives of phenylene ether compounds, phenylene ether compounds containing a maleic anhydride structure in the molecule, terminal hydroxyl-modified phenylene ether compounds, terminal methacryloyl-modified phenylene ether compounds, and terminal glycidyl ether-modified phenylene ether compounds. Product examples of arylene ether compounds containing a maleic anhydride structure in the molecule and having a weight average molecular weight of 30,000 or more include PME-80 and PME-82 manufactured by Mitsubishi Engineering-Plastics Corporation.
[0040] The arylene ether compound of the present invention preferably has a reactive unsaturated bond. Alternatively, the resin composition may further include another arylene ether compound having a reactive unsaturated bond. In this case, as another arylene ether compound, a weight average molecular weight of more than 30,000 is not required. That is, another arylene ether compound (although the weight average molecular weight can be more than 30,000) can be a weight average molecular weight less than 30,000, for example, a number average molecular weight of more than 500 and less than 10,000. Reactive unsaturated bonds are defined as unsaturated bonds that show reactivity through heat or ultraviolet rays. As preferred examples of reactive unsaturated bonds, cyanate groups, maleimide groups, vinyl groups, (meth) acryloyl groups, ethynyl groups, styryl groups and combinations thereof can be cited. From the viewpoint of high reactivity and controllable reaction (not easily causing reactions that occur over time, resins can be stored and can ensure that the product life is extended), styryl groups are particularly preferred.
[0041] From the viewpoint of showing high reactivity, it is preferred that the reactive unsaturated bond in the arylene ether compound is located at the end of the molecular structure or adjacent thereto. For example, as an example of a functional group having an unsaturated bond at the end of the molecular structure, 1,2-vinyl can be cited. Since 1,2-vinyl shows high reactivity, it is usually used as a functional group that can be used for free radical polymerization. On the other hand, in the case where there is an olefinic unsaturated bond (vinyl not located at the end of the molecular structure) in the molecular chain, its reactivity decreases. In addition, exceptionally, in the case where the benzene ring is adjacent to the unsaturated bond (such as the case of styryl), it has high reactivity. Therefore, the position of the reactive unsaturated bond can be a) the end of the molecular structure (whether the main chain or the side chain), and b) in the case where the benzene ring is located at the end of the molecular structure (whether the main chain or the side chain), it can also be a position adjacent to the benzene ring at the end. For example, the arylene ether compound can have styryl as a reactive unsaturated bond at both ends of the molecular structure. Product examples of the arylene ether compound having styryl groups at both molecular terminals include OPE-2St-1200 and OPE-2St-2200 manufactured by Mitsubishi Gas Chemical Co., Ltd. (however, the weight average molecular weight of the arylene ether compounds of these products is less than 30,000).
[0042] In the case where the resin composition of the present invention contains an arylene ether compound having a weight average molecular weight of 30,000 or more, the content thereof is not particularly limited, but from the viewpoint of taking into account both compatibility (related to peel strength) and dielectric properties, the content thereof is preferably 10 parts by weight or more and 90 parts by weight or less, more preferably 15 parts by weight or more and 80 parts by weight or less, and further preferably 20 parts by weight or more and 60 parts by weight or less, relative to 100 parts by weight of the total amount of the resin component (solid content). In this specification, the total amount of the resin component (solid content) of 100 parts by weight includes not only polymers and resins, but also the weight of additives such as reaction initiators that constitute a part of the resin is calculated, but the organic filler is not calculated.
[0043] The resin composition of the present invention preferably contains a styrene copolymer having a reactive unsaturated bond that is reactive by heat or ultraviolet rays in the molecule. The styrene copolymer may be optionally hydrogenated or non-hydrogenated. That is, the styrene copolymer is a compound containing a site derived from styrene, and is a polymer that may also contain a site derived from a compound having a polymerizable unsaturated group such as an olefin other than styrene. In the case where a double bond further exists at a site derived from a compound having a polymerizable unsaturated group of the styrene copolymer, the double bond portion may be hydrogenated or may not be hydrogenated. Examples of styrene copolymers include acrylonitrile-butadiene-styrene copolymers (ABS), methacrylate-butadiene-styrene copolymers (MBS), acrylonitrile-acrylate-styrene copolymers (AAS), acrylonitrile-ethylene-styrene copolymers (AES), styrene-butadiene copolymers (SBR), styrene-butadiene-styrene copolymers (SBS), styrene-ethylene-butadiene-styrene copolymers (SEBS), styrene / 4-methylstyrene / isoprene / butadiene block copolymers, and combinations thereof, preferably styrene-butadiene block copolymers (SBR), styrene / 4-methylstyrene / isoprene / butadiene block copolymers, and combinations thereof, and particularly preferably styrene / 4-methylstyrene / isoprene / butadiene block copolymers. The weight average molecular weight of the styrene copolymer is not particularly limited, but is preferably 40,000 to 400,000, more preferably 60,000 to 370,000, and particularly preferably 80,000 to 340,000.
[0044] The styrene copolymer used in the present invention has a reactive unsaturated bond in the molecule that is reactive by heat or ultraviolet rays. Preferred examples of the reactive unsaturated bond include cyanate groups, maleimide groups, terminal vinyl groups, (meth)acryloyl groups, ethynyl groups, styryl groups, and combinations thereof. From the viewpoint of high reactivity and controllable reaction (not prone to reaction over time, resin can be stored, and product life can be extended), styryl groups are particularly preferred.
[0045] From the viewpoint of showing high reactivity, it is preferred that the reactive unsaturated bond in the styrene copolymer is located at the end of the molecular structure or adjacent thereto. For example, as an example of a functional group having an unsaturated bond at the end of the molecular structure, 1,2-vinyl can be cited. Since 1,2-vinyl (terminal vinyl) shows high reactivity, it is usually used as a functional group that can be used for free radical polymerization. Therefore, it can be said that a styrene copolymer having such a functional group is a styrene copolymer having a reactive unsaturated bond in the molecule that is reactive by heat or ultraviolet rays. On the other hand, in the case where there is an ethylenic unsaturated bond (vinyl not located at the end of the molecular structure) in the molecular chain, its reactivity decreases. Therefore, it cannot be said that a styrene copolymer having such an unsaturated bond is a styrene copolymer having a reactive unsaturated bond in the molecule that is reactive by heat or ultraviolet rays. As a product example of a styrene copolymer that does not have an unsaturated bond at the end of the molecular structure, TR2003 manufactured by JSR Corporation can be cited. In addition, as an exception, when the benzene ring is adjacent to the unsaturated bond (for example, in the case of a styrene group), because of the high reactivity, it can be said that it is a styrene copolymer having a reactive unsaturated bond in the molecule that becomes reactive by heat or ultraviolet rays. Therefore, the position of the reactive unsaturated bond can be a) the end of the molecular structure (whether the main chain or the side chain), or b) when the benzene ring is located at the end of the molecular structure (whether the main chain or the side chain), it can also be a position adjacent to the terminal benzene ring. As an example of a product of a styrene copolymer having a reactive unsaturated bond, SEPTON manufactured by Kuraray Co., Ltd. can be cited. (R) V9461 (having a styryl group), Ricon manufactured by Cray Valley (R) 100, 181 and 184 (styrene-butadiene copolymers having 1,2-vinyl groups), EPOFRIEND AT501 and CT310 (styrene-butadiene copolymers having 1,2-vinyl groups) manufactured by Daicel Co., Ltd. It should be noted that "reactivity by heat or ultraviolet rays" means that reactivity is exhibited under heating conditions or ultraviolet irradiation conditions to the extent that a substrate (e.g., prepreg) suitable for use in combination with the resin composition of the present invention is cured, and the heating temperature under such conditions is generally about 160 to 230°C.
[0046] The styrene-based copolymer preferably has modified styrene butadiene. Alternatively, the resin composition may further contain another styrene-based copolymer having modified styrene butadiene. In this case, as another styrene-based copolymer, the same styrene-based copolymer as described above can be used except that it is not necessary to have a reactive unsaturated bond. That is, the other styrene-based copolymer (although it may be a copolymer having a reactive unsaturated bond, it may also be a copolymer not having a reactive unsaturated bond). The modified styrene butadiene is any styrene butadiene that is chemically modified by introducing various functional groups, for example, amine modification, pyridine modification, carboxyl modification, etc. can be listed, preferably amine modification. As an example of a styrene-based copolymer having modified styrene butadiene, Tuftec manufactured by Asahi Kasei Corporation, which is a hydrogenated styrene butadiene block copolymer and an amine-modified product, can be listed. (R) MP10. In addition, as an example of an unmodified styrene-based copolymer, TR2003 manufactured by JSR Corporation, which is a styrene-butadiene block copolymer, can be cited (however, MP10 and TR2003 are not styrene-based copolymers having a reactive unsaturated bond that is reactive with heat or ultraviolet rays in the molecule).
[0047] The content of the styrene-based copolymer having a reactive unsaturated bond that exhibits reactivity by heat or ultraviolet rays in the resin composition of the present invention is not particularly limited. From the viewpoint of achieving both compatibility and dielectric properties, the content is preferably 20 parts by weight or more and 99.5 parts by weight or less, more preferably 30 parts by weight or more and 90 parts by weight or less, and further preferably 40 parts by weight or more and 70 parts by weight or less, relative to 100 parts by weight of the total amount of the resin component (solid content).
[0048] The total content of the arylene ether compound having a weight average molecular weight of 30,000 or more and the styrene copolymer having a reactive unsaturated bond in the molecule that exhibits reactivity by heat or ultraviolet rays in the resin composition of the present invention is not particularly limited, but is preferably 30 parts by weight or more and 99.5 parts by weight or less, more preferably 40 parts by weight or more and 90 parts by weight or less, and further preferably 50 parts by weight or more and 85 parts by weight or less, relative to 100 parts by weight of the total amount of the resin component (solid content).
[0049] The resin composition of the present invention comprises an organic filler consisting of a liquid crystal polymer (LCP). By adding a liquid crystal polymer as a filler, not only can excellent dielectric properties be imparted to the resin composition, but also the high adhesion relative to the low roughness surface can be made not easy to deteriorate after thermal load. The performance of the thermal degradation can be suppressed, which is an advantage that inorganic fillers cannot obtain. In addition, the filler consisting of a liquid crystal polymer has excellent dispersibility to other resin components. For example, an organic filler made of polytetrafluoroethylene (PTFE) is difficult to disperse in a resin component, but an organic filler made of a liquid crystal polymer does not have this disadvantage and is advantageous in this respect. The organic filler is preferably in the form of liquid crystal polymer particles. Commercially available liquid crystal polymer particles can be used, for example, as a powder-grade liquid crystal polymer, XYDAR can be preferably used. (R) LF-31P (manufactured by ENEOS Co., Ltd.). The particle size of the liquid crystal polymer particles is not particularly limited as long as the desired performance can be exerted when dispersed in the resin composition as an organic filler. The average particle size D50 of the liquid crystal polymer particles is preferably 0.1 to 10 μm, more preferably 0.5 to 9 μm, and further preferably 1 to 8 μm. The average particle size D50 of the liquid crystal polymer particles can be measured by a laser diffraction scattering particle size distribution measuring device.
[0050] There is no particular limitation on the content of the organic filler; however, from the viewpoint of ease of filler dispersion, fluidity of the resin composition, etc., the content is preferably from 5 parts by weight to 300 parts by weight, more preferably from 10 parts by weight to 200 parts by weight, further preferably from 15 parts by weight to 200 parts by weight, particularly preferably from 15 parts by weight to 150 parts by weight, and most preferably from 25 parts by weight to 75 parts by weight, relative to 100 parts by weight of the total amount of the above-mentioned resin component (solid content).
[0051] The dielectric loss tangent of the organic filler at a frequency of 10 GHz is preferably 0.001 or less, more preferably 0.0009 or less, and further preferably 0.0008 or less. The dielectric loss tangent is preferably low, and the lower limit is not particularly limited, but is usually 0.0001 or more.
[0052] The resin composition of the present invention may contain additives generally added to resins and polymers. Examples of the additives include reaction initiators, reaction accelerators, flame retardants, silane coupling agents, dispersants, antioxidants, and the like.
[0053] Copper foil with resin
[0054] The resin composition of the present invention is preferably used as a resin of a copper foil with resin. That is, according to a preferred embodiment of the present invention, a copper foil with resin is provided, which comprises: a copper foil; and a resin layer containing a resin composition disposed on at least one surface of the copper foil. Generally speaking, the resin composition is in the form of a resin layer, and the resin composition is applied to the copper foil using a gravure coating method and dried so that the thickness of the dried resin layer is a specified value to obtain a copper foil with resin. Regarding the coating method, it is arbitrary, and in addition to the gravure coating method, a die coating method, a knife coating method, etc. can be used. In addition, a scraper, a rod coater, etc. can also be used for coating.
[0055] As mentioned above, resin combination of the present invention not only has excellent dielectric properties (such as low dielectric loss tangent at 10GHz) and high adhesion to low roughness surface (such as surface of low roughness copper foil), and after thermal load, can also stably maintain high adhesion relative to low roughness surface.Therefore, the copper foil with resin has the various advantages brought by this resin combination.For example, the copper foil with resin, when resin layer is cured state, is preferably more than 0.5kgf / cm according to the lower limit of the peel strength (i.e. normal peel strength) between the resin layer and the copper foil measured by JIS C6481-1996, more preferably more than 0.8kgf / cm, further preferably more than 1.0kgf / cm, especially preferably more than 1.2kgf / cm.Peel strength is high value better, and its upper limit is not particularly limited, and is generally below 2.0kgf / cm.
[0056] The thickness of the resin layer is not particularly limited. In order to ensure the peel strength, it is preferably thicker. The thickness of the laminated substrate is preferably thinner, so there is a suitable thickness. The thickness of the resin layer is preferably 1 μm or more and 50 μm or less, more preferably 1.5 μm or more and 30 μm or less, particularly preferably 2 μm or more and 20 μm or less, and most preferably 2.5 μm or more and 10 μm or less. By being within these ranges, the various characteristics of the present invention described above can be more effectively achieved, and the resin layer can be easily formed by coating the resin composition.
[0057] The copper foil may be a metal foil (so-called raw foil) manufactured by direct electrolysis or rolling, or may be a surface-treated foil in which at least one side thereof has been subjected to surface treatment. The surface treatment may be various surface treatments performed on the surface of the metal foil in order to improve or impart certain properties (such as rust resistance, moisture resistance, chemical resistance, acid resistance, heat resistance, and adhesion to the substrate). The surface treatment may be performed on a single side of the metal foil or on both sides of the metal foil. Examples of surface treatments performed on the copper foil include rust prevention treatment, silane treatment, roughening treatment, barrier layer formation treatment, and the like.
[0058] The ten-point height Rzjis of the microscopic roughness at the surface of the resin layer side of the copper foil measured according to JIS B0601-2001 is preferably 2.0 μm or less, more preferably 1.5 μm or less, further preferably 1.0 μm or less, particularly preferably 0.7 μm or less, and most preferably 0.5 μm or less. Within this range, the transmission loss in high-frequency applications can be ideally reduced. That is, the conductor loss caused by the copper foil can be reduced, and the conductor loss may increase due to the skin effect of the copper foil that becomes more and more significant with high frequency, thereby achieving a further reduction in transmission loss. There is no particular limitation on the lower limit of the ten-point height Rzjis of the microscopic roughness at the surface of the resin layer side of the copper foil. From the perspective of improving the adhesion with the resin layer and heat resistance, Rzjis is preferably 0.01 μm or more, more preferably 0.03 μm or more, and more preferably 0.05 μm or more.
[0059] The thickness of the copper foil is not particularly limited, but is preferably 0.1 μm or more and 100 μm or less, more preferably 0.5 μm or more and 70 μm or less, further preferably 1 μm or more and 50 μm or less, particularly preferably 1.5 μm or more and 30 μm or less, and most preferably 2 μm or more and 20 μm or less. When the thickness is within these ranges, it has the advantage of being able to form a fine circuit. Of course, when the thickness of the copper foil is, for example, 10 μm or less, the resin-bearing copper foil of the present invention can form a resin layer on the copper foil surface of the copper foil with a carrier having a peeling layer and a carrier in order to improve the handling property.
[0060] From the viewpoint of ensuring the closeness with the resin layer, the base material such as prepreg is preferably included in the resin with reactive unsaturated bonds in the molecule, and in addition, from the viewpoint of compatibility with the resin layer, it is preferably included polyphenylene ether resin. As a commercial example of a base material satisfying the resin with reactive unsaturated bonds in the molecule and the polyphenylene ether resin, the MEGTRON6 series, MEGTRON7 series, MEGTRON8 series, etc. of Panasonic Co., Ltd. can be cited. Such a low dielectric constant and low dielectric loss tangent base material listed here used to be difficult to ensure the closeness with the resin layer and even the low roughness copper foil, but by using the resin composition of the present invention, sufficient closeness can be ensured. In particular, high closeness can also be stably maintained relative to the low roughness copper foil after thermal load. Therefore, according to a preferred embodiment of the present invention, a laminate is provided, which is equipped with: a base material (such as a prepreg); and a resin layer (or a copper foil with resin of the present invention) comprising the resin composition of the present invention arranged on one or both sides of the base material.
[0061] Printed Circuit Board
[0062] The resin composition of the present invention and even the copper foil with resin are preferably used for the production of printed circuit boards. That is, according to a preferred embodiment of the present invention, a printed circuit board having the above-mentioned copper foil with resin or a printed circuit board made using the above-mentioned copper foil with resin is provided. In this case, the resin layer of the copper foil with resin is cured. The printed circuit board based on this embodiment comprises a layer structure in which insulating resin layers and copper layers are stacked in sequence. The printed circuit board can adopt a known layer structure. As specific examples of printed circuit boards, single-sided or double-sided printed circuit boards in which circuits are formed on the basis of a laminated body in which the copper foil with resin of the present invention is bonded to one or both sides of a prepreg and cured; multilayer printed circuit boards in which these printed circuit boards are multilayered, etc. In addition, as other specific examples, flexible printed circuit boards, COFs, TAB tapes, multilayer circuit boards by lamination, and direct stacking wafers in which copper foil with resin and circuits are formed are alternately and repeatedly stacked on semiconductor integrated circuits can be listed. In particular, the resin-coated copper foil of the present invention can be preferably used as an insulating layer and a conductive layer for a printed circuit board for high-frequency digital communication in network equipment. Examples of such network equipment include (i) servers and routers in base stations, (ii) internal company networks, and (iii) backbone systems for high-speed mobile communications.
[0063] Example
[0064] The present invention is further described in detail by the following examples.
[0065] Examples 1 to 12
[0066] (1) Preparation of resin varnish
[0067] First, as raw material components for a resin varnish, an arylene ether compound, a styrene copolymer, an additive, an organic filler, and an inorganic filler shown below are prepared.
[0068] <Arylene ether compound>
[0069] -OPE-2St-1200 (Mitsubishi Gas Chemical Co., Ltd., a phenylene ether compound having styryl groups at both ends of the molecule, number average molecular weight of about 1200)
[0070] -OPE-2St-2200 (Mitsubishi Gas Chemical Co., Ltd., a phenylene ether compound having styryl groups at both ends of the molecule, number average molecular weight of about 2200)
[0071] -PME-82 (Mitsubishi Engineering-Plastics Corporation, a phenylene ether compound containing a maleic anhydride structure in the molecule, with a weight average molecular weight of about 56,000)
[0072] <Styrene copolymer>
[0073] -SEPTON (R) V9461 (manufactured by Kuraray Co., Ltd., hydrogenated styrene / 4-methylstyrene / isoprene / butadiene block copolymer having styrene groups, weight average molecular weight about 296,000)
[0074] -TR2003 (manufactured by JSR Corporation, styrene butadiene block copolymer, weight average molecular weight about 95700)
[0075] -Tuftec (R) MP10 (manufactured by Asahi Kasei Corporation, hydrogenated styrene butadiene block copolymer, amine-modified product, weight average molecular weight about 60,000)
[0076] <Additives (reaction initiators)>
[0077] -PERBUTYL P (manufactured by NOF Corporation, peroxide)
[0078] <Inorganic fillers>
[0079] -SC4050-MOT (manufactured by Admatechs Co., Ltd., silica slurry, average particle size D50: 1.0 μm, surface vinyl silane treatment)
[0080] <Organic fillers>
[0081] -XYDAR (R) LF-31P (manufactured by ENEOS Corporation, liquid crystal polymer (LCP) powder, average particle size D50: 5 to 7 μm, dielectric loss tangent at 10 GHz: 0.0007)
[0082] The number average molecular weight and weight average molecular weight of the arylene ether compound and the styrene copolymer are values measured by GPC (gel permeation chromatography) under the following conditions. The molecular weights are relative values based on polystyrene.
[0083] Detector: Differential refractive index detector RI (manufactured by Tosoh Corporation, RI-8020, sensitivity 32)
[0084] Column: TSKgel GMH HR -M, 2 pieces (7.8 mm x 30 cm, manufactured by Tosoh Corporation)
[0085] Solvent: Chloroform
[0086] Flow rate: 1.0mL / min
[0087] Column temperature: 40℃
[0088] Injection volume: 0.2mL
[0089] · Standard sample: Monodisperse polystyrene, manufactured by Tosoh Corporation
[0090] Data processing: GPC data processing system manufactured by Toray Research Center
[0091] The above raw material components are weighed into a round flask according to the mixing ratio (weight ratio) shown in Table 1 and Table 2, and then a mixed solvent is added so that the solid content concentration derived from the raw material components is the value shown in Table 1 and Table 2. The mixed solvent is a solvent in which methyl ethyl ketone (MEK) and toluene are mixed at the MEK ratio (weight %) shown in Table 1 and Table 2. The round flask containing the raw material components and the mixed solvent is equipped with a mantle heater, a stirring blade and a flask cover with a reflux cooling tube, and the temperature is raised to 60°C while stirring, and then stirring is continued at 60°C for 2 hours to dissolve or disperse the raw material components. The resin varnish obtained after stirring is naturally cooled. Thus, a resin varnish with a solid content concentration shown in Table 1 and Table 2 is obtained.
[0092] (2) Production of electrolytic copper foil
[0093] Electrolytic copper foil was produced by the following method. In a copper sulfate solution, a titanium rotating electrode (surface roughness Ra: 0.20 μm) was used as the cathode and a dimensionally stable anode (DSA) was used as the anode. The solution temperature was 45°C and the current density was 55 A / dm 2 Electrolysis is performed to produce electrolytic copper foil as raw foil. The composition of the copper sulfate solution is 80 g / L copper concentration, 140 g / L free sulfuric acid concentration, 30 mg / L bis(3-sulfopropyl) disulfide concentration, 50 mg / L diallyldimethylammonium chloride polymer concentration, and 40 mg / L chlorine concentration. Granular protrusions are formed on the surface of the electrolyte side of the raw foil. The granular protrusions are formed by heating a copper sulfate solution (copper concentration: 13 g / L, free sulfuric acid concentration 55 g / L, 9-phenylacridine concentration 140 mg / L, chlorine concentration: 35 mg / L) at a solution temperature of 30°C and a current density of 50 A / dm 2 It is carried out by electrolysis under the conditions of
[0094] On the electrolyte surface side of the raw foil thus obtained, zinc-nickel coating formation, chromate layer formation, and silane layer formation were sequentially performed under the following conditions.
[0095] <Zinc-Nickel coating formation>
[0096] Potassium pyrophosphate concentration: 80g / L
[0097] Zinc concentration: 0.2g / L
[0098] Nickel concentration: 2g / L
[0099] ·Liquid temperature: 40℃
[0100] Current density: 0.5A / dm 2
[0101] <Chromate layer formation>
[0102] Chromic acid concentration: 1g / L, pH 11
[0103] Solution temperature: 25°C
[0104] Current density: 1A / dm 2
[0105] <Silane layer formation>
[0106] Silane coupling agent: 3-aminopropyltrimethoxysilane (3g / L aqueous solution)
[0107] Liquid treatment method: spray treatment
[0108] The microscopic roughness ten-point height Rzjis of the surface treated surface of the electrolytic copper foil was 0.5 μm (according to JIS B0601-2001), the average particle size of the granular protrusions measured by scanning electron microscope images was 100 nm, and the particle density was 205 pieces / μm. 2 The total thickness of the electrolytic copper foil including the surface treatment surface is 18μm.
[0109] (3) Preparation of resin film
[0110] The resin varnish obtained in (1) was applied onto a release film ("AFLEX" manufactured by AGC Corporation) using a comma knife coater. (R) ”) and dried in an oven at 150°C for 3 minutes so that the thickness of the dried resin was 20 μm to obtain a B-stage resin. The release film was peeled off from the obtained B-stage resin, and only two sheets of B-stage resin were stacked and heated at 200°C and 20 kgf / cm 2 Vacuum pressing was performed for 90 minutes under the conditions of , to obtain a resin film with a thickness of 40 μm.
[0111] (4) Fabrication of single-sided laminated substrate
[0112] The resin varnish obtained in (1) was applied to the surface of the electrolytic copper foil using a gravure coater and dried in an oven at 150°C for 2 minutes so that the thickness of the dried resin was 4 μm, thereby obtaining a copper foil with resin. A plurality of prepregs (manufactured by Panasonic Corporation, MEGTRON7 series "R-5680") were stacked to form a thickness of 0.2 mm, and the copper foil with resin was stacked so that the resin and the prepreg were in contact with each other, and heated at 190°C and 30 kgf / cm 2 Vacuum pressing was performed for 90 minutes under the conditions of to obtain a single-sided laminated substrate.
[0113] (5) Various evaluations
[0114] The produced resin films and single-sided laminated substrates were subjected to the following evaluations.
[0115] <Normal peel strength>
[0116] Copper wiring with a wiring width of 10 mm and a wiring thickness of 18 μm is formed on a single-sided laminate substrate by a subtractive method, and the peel strength (kgf / cm) is measured at room temperature (e.g., 25° C.) according to JIS C 6481-1996. The measurement was performed 5 times, and the average value is the value of the peel strength. It should be noted that the peel strength measured here is a value reflecting the four peeling modes of interface peeling between prepreg / resin, cohesive failure of resin, interface peeling in the resin layer, and interface peeling between resin / copper foil. The higher the value, the better the adhesion to the substrate such as prepreg, the strength of the resin layer, and the adhesion between the resin and the low roughness foil. As a result, as shown in Table 1 and Table 2, the normal peel strength in all examples 1 to 12 is 0.5 kgf / cm or more, confirming the high adhesion to the low roughness surface.
[0117] <Heat-resistant peel strength maintenance rate>
[0118] After forming a copper wiring with a wiring width of 10 mm and a wiring thickness of 18 μm on a single-sided laminate substrate by a subtractive method, it was floated in a solder bath at 288°C for 5 minutes for heat treatment. In addition, the post-heat peel strength (kgf / cm) was measured in the same steps as the above-mentioned normal peel strength. The heat-resistant peel strength maintenance rate (%) was calculated by dividing the value of the post-heat peel strength by the value of the above-mentioned normal peel strength and multiplying it by 100. The results are shown in Tables 1 and 2. It can be seen that the heat-resistant peel strength maintenance rate of the resin composition of Examples 1 to 7 is more than 95%, which is higher than Examples 8 to 12 (comparative examples), and can stably maintain high adhesion with low roughness surfaces even after heat load.
[0119] <Dielectric loss tangent>
[0120] The dielectric loss tangent of the resin film at 10 GHz was measured by the perturbation cavity resonator method. The measurement was performed in accordance with JIS R 1641 using a measuring device (a resonator manufactured by KEYCOM and a network analyzer manufactured by KEYSIGHT) after the resin film was cut to the sample size of the resonator. The results are shown in Tables 1 and 2.
[0121] [Table 1]
[0122]
[0123] [Table 2]
[0124]
Claims
1. A resin composition comprising: at least one of an arylene ether compound having a weight average molecular weight of 30,000 or more and a styrene-based copolymer having a reactive unsaturated bond in the molecule that exhibits reactivity by heat or ultraviolet rays, and Organic fillers composed of liquid crystal polymers.
2. The resin composition according to claim 1, wherein The reactive unsaturated bond is at least one selected from the group consisting of a cyanate group, a maleimide group, a terminal vinyl group, a (meth)acryloyl group, an ethynyl group, and a styryl group.
3. The resin composition according to claim 1 or 2, wherein The styrene-based copolymer has a styrene group as the reactive unsaturated bond.
4. The resin composition according to claim 1 or 2, wherein The resin composition contains both the arylene ether compound and the styrene-based copolymer.
5. The resin composition according to claim 1 or 2, wherein The dielectric loss tangent of the organic filler at a frequency of 10 GHz is less than 0.
001. 6 . A copper foil with resin, comprising: a copper foil; and a resin layer comprising the resin composition according to claim 1 or 2, which is provided on at least one surface of the copper foil.
7. The copper foil with resin according to claim 6, wherein A ten-point height Rzjis of microscopic roughness at the surface of the copper foil on the resin layer side measured in accordance with JIS B0601-2001 is 2.0 μm or less.
8. A printed wiring board produced using the copper foil with resin according to claim 6.
Citation Information
Patent Citations
Thermosetting resin composition, and resin varnish, prepreg and metal-clad laminate using the same
JP2011225639A
Copper foil with adhesive layer, copper-clad laminate and printed wiring board
WO2013105650A1
Resin composition, prepreg, laminate and multilayer printed wiring board
WO2016175326A1